Karakteristik Nades (Natural Deep Eutectic Solvent) - Novalia Rohulina Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
NADES is an environmentally friendly DES. DES (Deep Eutectic Solvent) is a eutectic compound formed from a mixture of HBA (Hydrogen Bond Acceptor) and HBD (Hydrogen Bond Donor) at a certain molar ratio with a lower melting point than its constituent components, so that DES can be prepared at low temperatures. Currently, DES is widely used in separation, catalysis, extraction and purification processes. DES preparation is relatively simple and can be made in two ways, namely by vacuum evaporation and heating. In general, the physico-chemical properties of DES depend on the type of HBA and HBA used. However, as research on DES develops, the physico-chemical properties also depend on the molecular interactions in DES. Molecular interactions can be analyzed using the FT-IR spectrum, based on the values of ΔH and GE. The smaller the values of ΔH and GE, the smaller the molecular interactions and the more stable the DES formed. Molecular dynamics simulations can be used to calculate the number of H-bonds, percent occupancy, and radial distribution functions in eutectic mixturesKeyword : characteristic, DES, HBA, HBD, NADES